A Study on Factors Affecting Students’ Choices of The English Proficiency Test as a Graduation Requirement at the university of Da Nang - university of foreign language studies - Nguyễn Thị Phương Thảo (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
writing of IELTS writing task 2. It seeks to provide an analysis of these writing errors at the discourse level by looking at the types of errors. In addition, it hopes to provide better insight into possible causes and give suggestions on how to avoid discourse errors